Primary oral malignant melanoma - A case report - K. Kumar; B. S. Santhosh; N. K. Priya (Nigerian Dental Association, 2011)
Melanoma arising from mucosal surfaces of the head and neck is a very rare neoplasm and it is considered among the most deadly of all human neoplasms. Although skin melanomas comprise 1.3% of all cancers, oral malignant melanoma accounts for only 0.2 to 8% of all reported melanomas, common sites of occurrence being palate and maxillary gingiva. Due to its presence at relatively obscure areas in the oral cavity, most oral malignant melanomas are diagnosed at a late stage and are associated with poor prognosis. Early diagnosis is essential for successful treatment and perhaps the key factor in improving the prognosis of oral malignant melanoma. This paper reports a case of a 42year old woman with primary malignant melanoma at a rare site, the left retromolar region involving the left side of the mandible, up to level IV ipsilateral cervical lymph nodes. The patient was treated with left hemimandibulectomy with radical neck dissection and was followed up for two years and 3months without any local recurrence or distant metastasis. It is suggested that any pigmented lesion that are suspected of undergoing changes in their clinical appearance should be biopsied.